ANALYSIS OF METHODS TO INCREASE BRAND LOYALTY AMONG RUSSIAN TELEVISION CHANNELS - M. Nemirovskaya; V. Yakusheva (Вестник университета)
Based on the study of marketing activities of Russian TV channels of entertainment and educational segments the modern methods of attracting viewers to television brands have been analyzed. The objects of the study are seven well-known public broadcasters, whose business has established more than twenty-five significant and cost-effective ways to influence the loyalty of the audience. In combination with negative factors indirectly affecting the implementation of loyalty programs, taking into account the existing methods of other industries, a minimum independent evaluation of the effectiveness of loyalty, which can serve as an idea for new marketing developments, and will contribute to the development of scientific research in this economical area, has been suggested.